Land Degradation Neutrality: A Pathway to Sustainable Land Management - Samatha, K.; Sree, Ch. Shushma; Amulya, P.; Hareesha, P.; Swapna, B.; Ramanjaneyulu, A. V.; Lakshmi, D. Vijaya; Ramesh, M.; Joseph, B. (Chronicle of Bioresource Management, 2026)
Land Degradation Neutrality (LDN) is an emerging global strategy aimed at halting and reversing the decline in land quality caused by human activities and natural processes. This paper discusses LDN as a sustainable framework to maintain or improve the amount and quality of productive land. Emphasizing the three key pillars avoidance, reduction, and reversal of land degradation, the study highlights the causes and types of land degradation viz., physical, chemical, biological, and ecological factors. The benefits of LDN such as improved ecosystem services, climate resilience, food security, and livelihoods, particularly in arid and semi-arid regions are outlined. India’s context is examined, revealing a significant proportion of degraded land and the urgent need for effective policy and action. By integrating restoration strategies and sustainable land management practices, LDN supports the achievement of Sustainable Development Goal 15.3 and contributes to global environmental stability.